Transparent and printed RF electronics: a comprehensive review of materials, and applications - Prabhakar Jepiti; Junghyeon Kim; Sumin Bark; Sungjoon Lim (Materials & Design)
The development of transparent radio-frequency (RF) electronics has enabled the creation of flexible, lightweight devices with novel applications. A key driver of this advancement is printed electronic devices, which offer scalable and environmentally friendly manufacturing methods. This study reviews recent progress in materials, fabrication techniques, and design strategies for transparent RF devices. The review examines critical materials, including conductive nanoparticle inks, conductive polymers, and emerging nanowire-based materials, and it assesses their electrical, mechanical, and optical properties. In addition, various printing technologies, such as inkjet, screen, electrohydrodynamic jet, offset, and roll-to-roll printing, are also evaluated for their ability to produce high-performance, miniaturised, and transparent RF devices. Current challenges, including the optimisation of conductivity, metallisation, transparency, and material durability, are also discussed. Finally, key application areas (such as antennas, metamaterial absorbers, and frequency-selective surfaces) are explored, with a focus on balancing transparency and functional performance. Finally, future challenges and opportunities are highlighted to encourage further research in this rapidly evolving field of transparent RF electronics.